Morphology-performance relationship of polypropylene-nanoclay composites processed by shear controlled injection moulding - Costantino, Alejandra (2013)
A nanoclay based masterbatch was mixed with polypropylene (PP) and injection moulded by conventional (CIM) and shear controlled orientation (SCORIM) injection moulding techniques. The aim was to correlate the morphologies induced by SCORIM and CIM processing with the thermal, mechanical and fracture performance of thick PP/nanoclay mouldings. In SCORIM, two extreme shear levels were applied by changing processing conditions. A complete characterization is reported, and statistical analysis was carried out to obtain a relationship between moulding properties. Nanoclay acted as a polymer morphology director, and in combinationwith SCORIM it induced the formation of the γ polymorph of PP. The nanoclay has a strong positive effectonthe thermal degradationofPPunder anoxidative atmosphere,dueto thebarrier effect of clayandthephysico-chemical adsorption of volatile degradation products on the silicates, but there were no differences between processing techniques. SCORIM samples of neat PP showed nonlinear brittle behaviour, while nanocomposites exhibited quasi-stable behaviour induced by a large deformation capability of the skin. Although fracture initiates at practically the same loading levels, the overall propagation energy values varied with processing conditions. Statistical analysis indicates that the decrement of the core region achieved by SCORIM processing, the differences between skin and core and the PP γ phase induced by the presence of nanoclay are responsible for the toughening of SCORIM PP/nanoclay mouldings.